A COOPERATIVE LEARNING STRATEGY USING SENTENCE PUZZLE MEDIA TO ENHANCE STUDENT ENGAGEMENT IN ARABIC READING INSTRUCTION - Ahmad Royhan Firdaus; Faris Ahmadi Wahib; Ahmad Muqfan Ahadi; Syaiful Mustofa (Al Ibrah: Journal of Arabic Language Education, 2026)
Arabic reading skill (Maharah Qira’ah) instruction in Islamic schools is frequently dominated by the grammar-translation approach, which often positions students as passive recipients of information. This condition may lead to limited student engagement in learning activities, particularly in emotional, cognitive, and social dimensions. This study aims to describe the implementation of a Cooperative Learning strategy using Sentence Puzzle media and to analyze student engagement in Arabic reading learning on the topic of Religions in Indonesia (Al-Adyān fī Indūnīsiyā) at MAN 2 Kota Batu. The study employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews with seven eleventh-grade students, classroom observations, and document analysis of lesson plans. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data reduction, data display, and conclusion drawing. The findings reveal that Cooperative Learning through Sentence Puzzle media enhances students’ emotional engagement, as reflected in increased enjoyment, enthusiasm, and learning motivation. Furthermore, the strategy promotes cognitive engagement through activities requiring text analysis, evaluation, and reconstruction, thereby fostering higher-order thinking skills. Socially, students demonstrated intensive collaborative interaction through discussion, meaning negotiation, and shared responsibility within groups. The study also found that students perceived the learning experience positively because it was meaningful, challenging, and enjoyable. These findings suggest that integrating Cooperative Learning with Sentence Puzzle media can serve as an innovative alternative for improving the quality of Arabic reading skill instruction in Islamic secondary education.